PERSEPSI MASYARAKAT TERHADAP MAKNA KIRAB KEBO BULE PADA PERINGATAN HAUL KI AGENG SINGOPRONO PADA BULAN SURA DI BOYOLALI - Adellia Ika Fadhillah Putri; Wahyu Firly Ramadhani; Alfian Dhani Kurnianto; Exi Engjelia Yessica; Melisa Ardini; Atika Lisamawati Nur Qoyyimah (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2025)
The perception of the Nglembu village community regarding the meaning of the Kebo Bule carnival on the commemoration of Ki Ageng Singoprono's haul resulted in a perception of the Kebo Bule ritual in one sura. Commemorating the haul in the Boyolali area for a year, a haul event was held to commemorate Ki Ageng Singoprono during his lifetime who spread Islam in the Boyolali area. This research aims to 1) explain the public's perception of the meaning of Kebo Bule at the Ki Ageng Singoprono haul commemoration carnival in the month of Sura; and 2) explaining the use of Kebo Bule in the commemoration ceremony for Ki Ageng Singoprono's haul in the month of Sura. This type of research uses a qualitative approach. The location in this research is Kalangan 01/01 Village, Nglembu, Simo, Boyolali. This research strategy is the technique of recording interview results. Data collection techniques in this research are observation, interviews and documentation. The results of this research show that 1) the Kebo Bule carnival is a symbol of the hope of the local community for safety, prosperity and well-being; and 2) A series of haul events followed by a group of Surakarta palace servants or soldiers starting the carnival followed by Kebo Kyai Slamet (Kebo Bule) along with his handler and Surakarta palace servants who carried palace heirlooms to the grave of Ki Ageng Singoprono.